2001
DOI: 10.1016/s0167-8809(00)00200-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional fertilization and its effect on corn insect populations in the Guatemalan highlands

Abstract: Cakchiquel farmers in Patzún, Guatemala stated that pest populations have increased in corn crops since they abandoned organic fertilization and adopted synthetic fertilizers. Given the dearth of scientific information about the effects of fertilization practices on pests, a controlled experiment was performed to elucidate these interactions. Pests, their natural enemies, and nutritional status were compared among corn plots with synthetic and organic fertilizers, and a control without fertilizer. Corn in fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 23 publications
(24 reference statements)
1
28
2
1
Order By: Relevance
“…Farmers in Patzun, Guatemala changed from organic fertilizers ("postura" of combining any available materials: ashes, lime, crop residues, weeds, and manure from goats, cows, horses, rabbits, and chickens in a mulch pile or well cow manure) by urea but observed the negative consequences of this change, with an increase in insect pests in the maize crops (Morales et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Farmers in Patzun, Guatemala changed from organic fertilizers ("postura" of combining any available materials: ashes, lime, crop residues, weeds, and manure from goats, cows, horses, rabbits, and chickens in a mulch pile or well cow manure) by urea but observed the negative consequences of this change, with an increase in insect pests in the maize crops (Morales et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In comparison to organic fertilizer, inorganic fertilizer contains more nitrogen that make plant cell contains more water favored by sucking insects. Previous study showed that infestation of aphids (Rhopalosiphummaidis) on corn in fields treated with organic fertilizer for at least 2 years was lower than corn treated with synthetic fertilizer [19]. It is suggested that nitrogen stimulates insect reproduction.…”
Section: Chinese Cabbage Resistance Against Pestsmentioning
confidence: 99%
“…They also fault individual farmers for not diversifying their crops, or not using organic methods, or using wrongheaded "traditional" practices, like burning their fields before planting, which removes more nutrients. Studies show, for example, that new pests result from adaptive resistance to pesticides or from the depletion of soil nutrients (Morales et al 2000). If they mention it at all, agronomists attribute input cost inflation to impersonal market forces of supply and demand.…”
Section: Expert Discourses On the Crisis In Subsistence Agriculturementioning
confidence: 99%